Maps of Family Relationships Drawn by Women Engaged in Bisexual Motherhood: Defining Family Membership. (December 2018) - Tasker, Fiona; Delvoye, Marie
Family building by bisexual mothers is a neglected area of research, yet this is an important aspect of life course development that may reciprocally influence the sexual identity development of bisexual women and family processes around parenting. Family map drawings (genograms) and interview data were collected from eight cisgender women from the United Kingdom and Republic of Ireland who spoke about their bisexual parenting experience and family relationships. Thematic narrative analysis indicates that participants depict both heteronormative (traditional) extended kinship networks (radiating out from a family core centering on them and their children) and family of choice network features. Nonetheless certain features appear to be more indirectly presented on some participants' family maps: namely, complex or marginalized (erased) relationships with additional partners that may sustain sexual identity but contradict both heteronormative and homonormative presentations of family life. Our discussion considers the difficult issues bisexual mothers face in maintaining both their family relationships and a marginalized sexual identity.